Evaluating Risk Communication Strategies in Local Government Responses to Dengue Fever in Indonesia - Febriana, Ajeng Iva Dwi; Selawaty, Desy (Communica : Journal of Communication, 2025)
Dengue fever remains a pressing public health challenge in Indonesia, where rapid urbanization, climate variability, and limited vector control capacity exacerbate transmission risks. This study aims to evaluate the effectiveness of local government risk communication strategies through a mixed-methods comparative case study of three initiatives: Bandung’s CeWoli Jawara, Banjarmasin’s PSN 3M Plus, and Tabanan’s PMI model. Findings reveal that multichannel and participatory strategies particularly those integrating digital tools with community-based outreach strengthen message retention, build public trust, and improve behavioral compliance. Trusted messengers such as health cadres and peer educators enhance credibility, while feedback loops and message repetition sustain engagement. In contrast, top-down approaches with limited interactivity often reduce effectiveness. The novelty of this research lies in its systematic comparison of localized communication models, combining global frameworks such as WHO’s RCCE principles with Indonesia’s own communication traditions. The results highlight how culturally attuned, community-driven communication can bridge gaps in public health governance. For policymakers, the study recommends embedding participatory infrastructures, investing in trusted local communicators, and institutionalizing hybrid media ecosystems to ensure resilience against future vector-borne outbreaks.